Edukasi Gizi dan Food Plating Isi Piringku Pada Ibu Hamil Cegah Stunting - Rista Dwi Hermilasari; Meisyenda Cahyani; Shabrina Salsabila; Inesa Malika Dewi; Veda Vania Syahda; Dola Elisa Silitonga; Naomi Azka Syehan; Feny Sabdaniyah (Jurnal Abdimas Kesehatan (JAK), 2026)
Nutrition for pregnant women is important to support optimal fetal growth and development. Mothers who experience nutritional deficiencies during pregnancy due to poor nutritional intake are at greater risk for delivering birth to infants with a low birth weight, stunted toddlers, and also suffering from chronic energy deficiency. As a result, it's essential for giving better close attention to the quality of nutritional intake for pregnant women in Tangsil Wetan Village. The purpose of this program of community service is to empower women who are pregnant regarding the fulfillment of balanced nutritional needs in a strategy for preventing stunting during pregnancy. There were 20 pregnant women who participated in this activity. The method being applied to this community service is counseling with lectures accompanied by questions and answers as well as a demonstration of serving food portions. Implementation of pre-test and post-test for assessing the knowledge of participants. Regarding the outcomes of the pre-posttest, it was shown that the level of knowledge of pregnant women risen significantly with an increase of 25.81%. The results of the demonstration activity on serving food portions according to the contents of my plate can increase understanding for pregnant women to know the right food portion standards. From the results of this activity, ongoing mentoring efforts are needed for pregnant women to prevent stunting, especially balanced nutritional education, especially determining meal portions